RETRACTED: Exploring the Effects of Natural Capital Depletion and Natural Disasters on Happiness and Human Wellbeing: A Study in China - Lu, Fami; Sohail, Muhammad Tayyab (Frontiers in Psychology, 2022)
Since recent climate change has caused more natural disasters than ever before, there is a worldwide concern that this could have both short-term and long-term economic and health consequences. Perhaps, this is the first attempt to explores the effects of natural capital and natural disasters on the human health & wellbeing of China over the period 1993–2020. The study has compiled data from World Bank, World Value Survey, UNDP, EM-DAT, and IMF for analysis. The empirical analysis is done by using the autoregressive distributed lag (ARDL) model. Empirical results prove that natural capital has a positive and significant effect on happiness, health, and human wellbeing in the long-run. The results also show that natural disasters significantly reduce happiness and human well-being in the long-run. The results recommend some important policy implications.